Implementation of Tangible Fixed Assets Recording in the Company - Andini Molia (International Publisher, 2022)
Basically a company is always trying to achieve the goals of the establishment of the company. Various kinds of supporting tools are sought so that these goals can be achieved. One of them is the existence of tangible fixed assets that function to facilitate company activities. Correct recording in buying tangible fixed assets aims to provide information in the future. Likewise depreciation, if the depreciation method and calculations are applied consistently it will be very easy to trace the accumulated depreciation. This study aims to determine the recording of tangible fixed assets, then to determine the calculation and method of depreciation of fixed assets applied at CV Andilia Jovito. And also to find out the recording of changes in the value of tangible fixed assets from rupiah to dollars as a result of changes in the accounting books used. The writing method used is descriptive qualitative, namely describing, analyzing, and understanding the existing data and then describing it in the form of words, numbers, and conclusions. The results of this study are that the application of recording fixed assets applied by CV Andilia Jovito is consistent, the depreciation method used is the straight-line method, and the change in bookkeeping from rupiah to dollars results in a change in the acquisition price of tangible fixed assets.